Healthcare provider perspectives on managing sexually transmitted infections in HIV care settings in Kenya: A qualitative thematic analysis - Chesang, Kipruto; Hornston, Sureyya; Muhenje, Odylia; Saliku, Teresa; Mirjahangir, Joy; Viitanen, Amanda; Musyoki, Helgar; Awuor, Christine; Githuka, George; Bock, Naomi (PLOS Medicine, 2017)
Background The burden of sexually transmitted infections (STIs) has been increasing in Kenya, as is the case elsewhere in sub-Saharan Africa, while measures for control and prevention are weak. The objectives of this study were to (1) describe healthcare provider (HCP) knowledge and practices, (2) explore HCP attitudes and beliefs, (3) identify structural and environmental factors affecting STI management, and (4) seek recommendations to improve the STI program in Kenya. Methods and findings Using individual in-depth interviews (IDIs), data were obtained from 87 HCPs working in 21 high-volume comprehensive HIV care centers (CCCs) in 7 of Kenya’s 8 regions. Transcript coding was performed through an inductive and iterative process, and the data were analyzed using NVivo 10.0. Overall, HCPs were knowledgeable about STIs, saw STIs as a priority, reported high STI co-infection amongst people living with HIV (PLHIV), and believed STIs in PLHIV facilitate HIV transmission. Most used the syndromic approach for STI management. Condoms and counseling were available in most of the clinics. HCPs believed that having an STI increased stigma in the community, that there was STI antimicrobial drug resistance, and that STIs were not prioritized by the authorities. HCPs had positive attitudes toward managing STIs, but were uncomfortable discussing sexual issues with patients in general, and profoundly for anal sex. The main barriers to the management of STIs reported were low commitment by higher levels of management, few recent STI-focused trainings, high stigma and low community participation, and STI drug stock-outs. Solutions recommended by HCPs included formulation of new STI policies that would increase access, availability, and quality of STI services; integrated STI/HIV management; improved STI training; increased supervision; standardized reporting; and community involvement in STI prevention. The key limitations of our study were that (1) participant experience and how much of their workload was devoted to managing STIs was not considered, (2) some responses may have been subject to recall and social desirability bias, and (3) patients or clients of STI services were not interviewed, and therefore their inputs were not obtained. While considering these limitations, the number and variety of facilities sampled, the mix of staff cadres interviewed, the use of a standardized instrument, and the consistency of responses add strength to our findings. Conclusions This study showed that HCPs understood the challenges of, and solutions for, improving the management of STIs in Kenya. Commitment by higher management, training in the management of STIs, measures for reducing stigma, and introducing new policies of STI management should be considered by health authorities in Kenya.